2021
DOI: 10.3390/nu13103421
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and Exercise in Oncology: Potential Synergism of Combined Interventions

Abstract: Nutrition and exercise interventions are strongly recommended for most cancer patients; however, much debate exists about the best prescription. Combining fasting with exercise is relatively untouched within the oncology setting. Separately, fasting has demonstrated reductions in chemotherapy-related side effects and improved treatment tolerability and effectiveness. Emerging evidence suggests fasting may have a protective effect on healthy cells allowing chemotherapy to exclusively target cancer cells. Exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 147 publications
(221 reference statements)
0
1
0
Order By: Relevance
“…When exercising in a fed state, the body primarily utilizes glucose from the recent diet as the predominant source of fuel. However, when exercising in a fasted state, as a result of the depletion of glucose and glycogen stores, the preferential fuel comes from lipolysis and fat oxidation, particularly the breakdown of intramyocellular triglycerides, resulting in stronger beneficial actions for metabolic health [ 77 ]. Some studies revealed that the combination of IF and exercise increased mitochondrial activity, exacerbated the consumption of stored lipids, and enhanced the lipid reserves in muscle [ 78 ].…”
Section: Modulation Effects Of Combining If and Physical Exercise On ...mentioning
confidence: 99%
“…When exercising in a fed state, the body primarily utilizes glucose from the recent diet as the predominant source of fuel. However, when exercising in a fasted state, as a result of the depletion of glucose and glycogen stores, the preferential fuel comes from lipolysis and fat oxidation, particularly the breakdown of intramyocellular triglycerides, resulting in stronger beneficial actions for metabolic health [ 77 ]. Some studies revealed that the combination of IF and exercise increased mitochondrial activity, exacerbated the consumption of stored lipids, and enhanced the lipid reserves in muscle [ 78 ].…”
Section: Modulation Effects Of Combining If and Physical Exercise On ...mentioning
confidence: 99%